Metal-clad laminated plate, and manufacturing method therefor

By adjusting the physical properties of the inorganic filler layer and adhesion layer in metal interlayer coating, the problems of hollow elimination and adhesion are solved, and the stability and thickness uniformity of the adhesive layer are achieved, which is suitable for high-frequency communication circuit board materials.

JP2025049784APending Publication Date: 2025-04-04NIPPON STEEL CHEM & MATERIAL CO LTD

Patent Information

Application Number
JP2023158180
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the manufacture of metal interlayer coatings, it is difficult to simultaneously eliminate holes in the seamless layer and ensure adhesion of the metal foil while preventing the flow and uneven thickness of the adhesive layer.

Method used

By adjusting the melting point of the inorganic filler content layer and the melting point or storage modulus of the adhesion layer, ensure that the melting point of the adhesion layer is higher than the melting point or glass transition point of the inorganic filler layer, and the storage modulus of the adhesion layer is controlled during the hot pressing process to prevent uneven flow and thickness of the adhesion layer.

Benefits of technology

It effectively eliminates the voids in the inorganic filler layer, ensures good adhesion of the metal foil, and prevents the flow and thickness of the adhesive layer. It is suitable for circuit board materials of high-frequency communication standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025049784000001_ABST
    Figure 2025049784000001_ABST
Patent Text Reader

Abstract

To achieve both elimination of voids in an inorganic filler-containing resin layer, and assurance of adhesion to a metal foil, while not only preventing an adhesive layer from flowing out during thermocompression bonding but also preventing generation of thickness unevenness.SOLUTION: According to a metal-clad laminated plate 100 obtained by laminating a metal layer 10A, an adhesive layer 20A, an inorganic filler-containing resin layer 30, an adhesive layer 20B, and a metal layer 10B in this order, the adhesive layer and the inorganic filler-containing resin layer each are constituted from either a crystalline resin or a non-crystalline resin, and satisfy any of the following conditions: a) a melting point Tm1 of a main resin in the adhesive layer is higher than a melting point Tm2 of the inorganic filler-containing resin layer; b) the melting point Tm1 of the main resin in the adhesive layer is higher than a glass transition point Tg2 of the inorganic filler-containing resin layer; c) a storage elastic modulus E' of the adhesive layer at a melting point Tm2 of the inorganic filler-containing resin layer is 1×106 Pa or more; and d) the storage elastic modulus E' of the adhesive layer at the glass transition point Tg2 of the inorganic filler-containing resin layer is 1×106 Pa or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a metal-clad laminate that is useful, for example, as a circuit board material. [Background technology]

[0002] In recent years, with the progress of miniaturization, weight reduction, and space saving of electronic devices, there is an increasing demand for flexible printed circuits (FPCs) that are thin, lightweight, flexible, and have excellent durability even when repeatedly bent. Because FPCs allow three-dimensional and high-density mounting even in a limited space, their applications are expanding to include wiring for electronic devices such as HDDs, DVDs, and smartphones, as well as components such as cables and connectors.

[0003] FPCs are manufactured by etching the metal layer of metal-clad laminates such as copper-clad laminates (CCL) and processing the wiring. Currently, metal-clad laminates that use highly heat-resistant polyimide for the insulating resin layer that contacts the metal foil are widely used. However, with the increasing speed of communication devices in recent years, the development of 5G and even 6G communication is progressing, and circuit board materials are also being investigated for millimeter wave radar boards and antenna boards that can support high-speed communication standards. Such materials, such as fluororesins and liquid crystal polymers, have attracted attention as materials with low dielectric tangents and are expected to reduce signal transmission loss.

[0004] Even if the resin has a low dielectric tangent, when the thermal expansion coefficient is large, the incorporation of inorganic fillers has been investigated to achieve low thermal expansion, which is a required characteristic of insulating materials for circuit boards. However, there is a problem that high loading of inorganic fillers reduces adhesion to low-roughening copper foil (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6997104 Summary of the Invention [Problem to be solved by the invention]

[0006] In Patent Document 1, in the process of producing a composite material layer containing an inorganic filler in a fluororesin matrix, a casting process is carried out in which a dispersion composition containing a fluororesin and an inorganic filler is applied to a substrate and dried. When a composite material containing an inorganic filler is formed in this way by a casting process, voids are generated in the coating film. In order to eliminate the voids, it is necessary to heat the composite material by thermocompression while applying heat equal to or higher than the flow temperature of the composite material. However, when an adhesive layer is formed in advance on a metal foil and a coating film is formed thereon, it is necessary to consider both the suppression of flow of the adhesive layer and the elimination of voids in the composite material layer. In other words, when an adhesive layer is provided, there is a concern that it is difficult to simultaneously eliminate voids and suppress the flow of the adhesive layer and the unevenness of the thickness. In this regard, Patent Document 1 does not provide anything that is clearly positioned as an adhesive layer adjacent to the metal layer, so the suppression of flow of the adhesive layer is not taken into consideration.

[0007] Therefore, an object of the present invention is to eliminate voids in an inorganic filler-containing resin layer and ensure adhesion to a metal foil while preventing the adhesive layer from flowing out or having uneven thickness during thermocompression bonding. [Means for solving the problem]

[0008] In view of the above situation, we conducted intensive research and discovered that the above problem can be solved by focusing on the melting point of the inorganic filler-containing resin layer and taking into consideration the relationship between this melting point and the melting point or storage modulus of the adhesive layer, thereby completing the present invention.

[0009] That is, the metal-clad laminate of the present invention comprises a metal layer and an adhesive layer directly in contact with the metal layer; an inorganic filler-containing resin layer that contains an inorganic filler in a resin and is laminated directly or indirectly on the adhesive layer; The metal-clad laminate of the present invention is characterized in that the adhesive layer and the inorganic filler-containing resin layer are provided with the following a) to d): a) when the main resin constituting the adhesive layer is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer is a crystalline resin, the melting point Tm1 of the main resin constituting the adhesive layer is higher than the melting point Tm2 of the inorganic filler-containing resin layer; b) when the main resin constituting the adhesive layer is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer is an amorphous resin, the melting point Tm1 of the main resin constituting the adhesive layer is higher than the glass transition point Tg2 of the inorganic filler-containing resin layer; c) When the main resin constituting the adhesive layer is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer is a crystalline resin, the storage modulus E' of the adhesive layer at the melting point Tm2 of the inorganic filler-containing resin layer is 1×10 6 Pa or more; d) When the main resin constituting the adhesive layer is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer is an amorphous resin, the storage modulus E' of the adhesive layer at the glass transition temperature Tg2 of the inorganic filler-containing resin layer is 1×10 6 Pa or more; Either of the following conditions is met: The entire insulating layer including the adhesive layer and the inorganic filler-containing resin layer has a coefficient of thermal expansion (CTE) of 60 ppm / K or less.

[0010] The metal-clad laminate of the present invention may have a dielectric loss tangent of less than 0.0025 at 20 GHz measured using a split post dielectric resonator (SPDR resonator) after leaving the entire insulating layer including the adhesive layer and the inorganic filler-containing resin layer for 24 hours under conditions of temperature: 24 to 26°C and humidity: 45 to 55%.

[0011] The metal-clad laminate of the present invention may have a layer structure in which a metal layer / an adhesive layer / an inorganic filler-containing resin layer / an adhesive layer / a metal layer are laminated in this order.

[0012] In the metal-clad laminate of the present invention, the ratio of the thickness of the adhesive layer to the total thickness of the adhesive layer and the inorganic filler-containing resin layer may be within a range of 1 to 25%.

[0013] In the metal-clad laminate of the present invention, when the inorganic filler-containing resin layer is formed into a film together with the main resin, the storage modulus at 50°C may be 2500 MPa or less, and the maximum storage modulus in the temperature range from 180°C to 260°C may be 800 MPa or less.

[0014] The method for producing a metal-clad laminate of the present invention is a method for producing the above-mentioned metal-clad laminate, A step of preparing a first laminate having an adhesive layer laminated on a metal layer; A step of applying a dispersion composition containing an inorganic filler and a powder of the main resin onto the adhesive layer, and heat-treating the dispersion composition to form a second laminate in which the adhesive layer and the dispersion composition layer are laminated on the metal layer; A step of forming a metal-clad laminate having a layer structure in which a metal layer / an adhesive layer / an inorganic filler-containing resin layer / an adhesive layer / a metal layer are laminated in this order by using two of the second laminates and thermocompressing the dispersion composition layers facing each other, or by using the first laminate and the second laminate and thermocompressing the adhesive layer and the dispersion composition layer facing each other; Contains Effect of the Invention

[0015] In the metal-clad laminate of the present invention, the melting point Tm1 or storage modulus E' of the main resin constituting the adhesive layer is taken into consideration in relation to the melting point Tm2 or glass transition point Tg2 of the inorganic filler-containing resin layer, so that the adhesive layer is prevented from flowing out or having uneven thickness during thermocompression bonding, while eliminating voids in the inorganic filler-containing resin layer and ensuring adhesion to the metal foil. Therefore, the metal-clad laminate of the present invention is useful as a circuit board material that can comply with high-speed communication standards. [Brief description of the drawings]

[0016] [Figure 1] 1 is a schematic cross-sectional view showing a layer structure of a metal-clad laminate according to a preferred embodiment of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram of a manufacturing process of the metal-clad laminate of FIG. [Diagram 3] 1. FIG. 4 is an explanatory diagram of another manufacturing process for the metal-clad laminate of FIG. [Figure 4] 1. FIG. 4 is an explanatory diagram of still another manufacturing process for the metal-clad laminate of FIG. [Diagram 5] 1. FIG. 4 is an explanatory diagram of still another manufacturing process for the metal-clad laminate of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of the present invention will be described with reference to the accompanying drawings.

[0018] [Metal-clad laminate] The metal-clad laminate of the present invention includes a metal foil, an adhesive layer in direct contact with the metal foil, and an inorganic filler-containing resin layer that contains an inorganic filler and is laminated directly or indirectly on the adhesive layer. The metal-clad laminate of the present invention may include any layer other than those described above.

[0019] The metal-clad laminate of the present invention satisfies any one of the following conditions a) to d). In the present invention, the term "main resin" means, in the case of an adhesive layer, a resin contained in an amount of more than 50% by weight, preferably 70% by weight or more, more preferably 80% by weight or more, and most preferably 90% by weight or more, of the total resin components constituting the adhesive layer. In the case of an inorganic filler-containing resin layer, the term "main resin" means, in the case of an inorganic filler-containing resin layer, a resin contained in an amount of more than 50% by weight, preferably 60% by weight or more, of the total resin components constituting the inorganic filler-containing resin layer (the same applies below).

[0020] Condition A): When the main resin constituting the adhesive layer is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer is a crystalline resin, the melting point Tm1 of the main resin constituting the adhesive layer is higher than the melting point Tm2 of the inorganic filler-containing resin layer. By having the melting point Tm1 higher than the melting point Tm2 (Tm1>Tm2), it is possible to effectively prevent the adhesive layer from flowing out or the thickness from being uneven when the adhesive layer is thermocompressed at a temperature above the melting point Tm2 to eliminate the voids in the inorganic filler-containing resin layer. Therefore, in the metal-clad laminate, it is possible to reduce the voids in the inorganic filler-containing resin layer and ensure adhesion to the metal foil while preventing the adhesive layer from flowing out or the thickness from being uneven. On the other hand, if the melting point Tm1 is the same as or lower than the melting point Tm2 (Tm1≦Tm2), there is a risk that the adhesive layer will flow out or the thickness will be uneven when the adhesive layer is thermocompressed at a temperature above the melting point Tm2. From the above viewpoints, the melting point Tm1 of the adhesive layer is preferably higher than the melting point Tm2 of the inorganic filler-containing resin layer by +5°C or more, more preferably higher by +10°C or more.

[0021] The melting point Tm2 is referred to as the "melting point of the inorganic filler-containing resin layer" rather than the "melting point of the main resin constituting the inorganic filler-containing resin layer" because, even if it is the same resin, when it contains inorganic filler, the melting point is higher due to the effect of the resin being restrained by the inorganic filler compared to when it does not contain inorganic filler, and the ease of melting changes due to the effect of resin components other than the main resin. Therefore, it is referred to as the melting point of the "layer" containing inorganic filler, etc., rather than the resin alone.

[0022] A preferred combination of resins in which the melting point Tm1 of the crystalline resin that is the main resin constituting the adhesive layer is higher than the melting point Tm2 of the inorganic filler-containing resin layer is, for example, A combination in which the main resin constituting the adhesive layer is a fluorine-based resin and the main resin constituting the inorganic filler-containing resin layer is a liquid crystal polymer; A combination in which the main resin constituting the adhesive layer is a fluorine-based resin and the main resin constituting the inorganic filler-containing resin layer is polyphenylene sulfide; A combination in which the main resin constituting the adhesive layer is a fluorine-based resin and the main resin constituting the inorganic filler-containing resin layer is polyether ether ketone; A combination in which the main resin constituting the adhesive layer is a fluororesin and the main resin constituting the inorganic filler-containing resin layer is syndiotactic polystyrene; A combination in which the main resin constituting the adhesive layer is polyether ether ketone and the main resin constituting the inorganic filler-containing resin layer is a liquid crystal polymer; A combination in which the main resin constituting the adhesive layer is polyether ether ketone and the main resin constituting the inorganic filler-containing resin layer is polyphenylene sulfide; A combination in which the main resin constituting the adhesive layer is polyether ether ketone and the main resin constituting the inorganic filler-containing resin layer is syndiotactic polystyrene; A combination in which the main resin constituting the adhesive layer is polyphenylene sulfide and the main resin constituting the inorganic filler-containing resin layer is syndiotactic polystyrene; A combination in which the main resin constituting the adhesive layer is syndiotactic polystyrene and the main resin constituting the inorganic filler-containing resin layer is polyphenylene sulfide; Some examples include:

[0023] Condition b): When the main resin constituting the adhesive layer is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer is an amorphous resin, the melting point Tm1 of the main resin constituting the adhesive layer is higher than the glass transition point Tg2 of the inorganic filler-containing resin layer. By having the melting point Tm1 higher than the glass transition point Tg2 (Tm1>Tg2), it is possible to effectively prevent the adhesive layer from flowing out or the thickness from being uneven when the adhesive layer is thermocompressed at a temperature above the glass transition point Tg2 to eliminate the voids in the inorganic filler-containing resin layer. Therefore, in the metal-clad laminate, it is possible to reduce the voids in the inorganic filler-containing resin layer and ensure adhesion to the metal foil while preventing the adhesive layer from flowing out or the thickness from being uneven. On the other hand, if the melting point Tm1 is the same as or lower than the glass transition point Tg2 (Tm1≦Tg2), there is a risk that the adhesive layer will flow out or the thickness will be uneven when the adhesive layer is thermocompressed at a temperature above the glass transition point Tg2. From the above viewpoints, the melting point Tm1 of the main resin constituting the adhesive layer is preferably higher than the glass transition point Tg2 of the inorganic filler-containing resin layer by +5°C or more, more preferably higher than +10°C or more.

[0024] The glass transition point Tg2 is referred to as "the glass transition point of the inorganic filler-containing resin layer" rather than "the glass transition point of the main resin constituting the inorganic filler-containing resin layer" because, even if the resin is the same, when the inorganic filler is contained, the glass transition point becomes higher due to the influence of the inorganic filler compared to when the inorganic filler is not contained, and the glass transition point changes due to the influence of resin components other than the main resin.

[0025] Examples of the combination of resins in which the melting point Tm1 of the main resin constituting the adhesive layer is higher than the glass transition point Tg2 of the inorganic filler-containing resin layer include: A combination in which the main resin constituting the adhesive layer is a fluorine-based resin and the main resin constituting the inorganic filler-containing resin layer is polyphenylene ether; A combination in which the main resin constituting the adhesive layer is polyphenylene sulfide and the main resin constituting the inorganic filler-containing resin layer is polyphenylene ether; A combination in which the main resin constituting the adhesive layer is polyether ether ketone and the main resin constituting the inorganic filler-containing resin layer is polyphenylene ether; A combination in which the main resin constituting the adhesive layer is syndiotactic polystyrene and the main resin constituting the inorganic filler-containing resin layer is polyphenylene ether; A combination in which the main resin constituting the adhesive layer is a fluorine-based resin and the main resin constituting the inorganic filler-containing resin layer is a polyimide; A combination in which the main resin constituting the adhesive layer is polyphenylene sulfide and the main resin constituting the inorganic filler-containing resin layer is polyimide; A combination in which the main resin constituting the adhesive layer is polyether ether ketone and the main resin constituting the inorganic filler-containing resin layer is polyimide; A combination in which the main resin constituting the adhesive layer is syndiotactic polystyrene and the main resin constituting the inorganic filler-containing resin layer is polyimide; A combination in which the main resin constituting the adhesive layer is syndiotactic polystyrene and the main resin constituting the inorganic filler-containing resin layer is polyimide; A combination in which the main resin constituting the adhesive layer is a fluororesin and the main resin constituting the inorganic filler-containing resin layer is a cycloolefin polymer; A combination in which the main resin constituting the adhesive layer is polyphenylene sulfide and the main resin constituting the inorganic filler-containing resin layer is cycloolefin polymer; A combination in which the main resin constituting the adhesive layer is polyether ether ketone and the main resin constituting the inorganic filler-containing resin layer is a cycloolefin polymer; A combination in which the main resin constituting the adhesive layer is syndiotactic polystyrene and the main resin constituting the inorganic filler-containing resin layer is a cycloolefin polymer; A combination in which the main resin constituting the adhesive layer is syndiotactic polystyrene and the main resin constituting the inorganic filler-containing resin layer is a cycloolefin polymer; Some examples include: In the present invention, the term "polyimide" is used to include polyetherimide, polyesterimide, polyamideimide, and the like.

[0026] Condition c): When the main resin constituting the adhesive layer is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer is a crystalline resin, the storage modulus E' of the adhesive layer at the melting point Tm2 of the inorganic filler-containing resin layer is 1×10 6 Must be Pa or higher. The storage modulus E' of the adhesive layer at the melting point Tm2 is 1×10 6 By having a storage modulus E' of 1 x 10 Pa or more, it is possible to effectively prevent the adhesive layer from flowing out or having uneven thickness when performing thermocompression bonding at a temperature above the melting point Tm2 to eliminate voids in the inorganic filler-containing resin layer. Therefore, in a metal-clad laminate, it is possible to reduce voids in the inorganic filler-containing resin layer and ensure adhesion to the metal foil while preventing the adhesive layer from flowing out or having uneven thickness. In contrast, when the storage modulus E' of the adhesive layer at the melting point Tm2 is 1 x 10 6 If it is less than Pa, there is a risk that the adhesive layer will flow out or have uneven thickness during thermocompression bonding at a temperature exceeding the melting point Tm2.

[0027] The storage modulus E' of the adhesive layer at the melting point Tm2 of the inorganic filler-containing resin layer is 1×10 6 Examples of preferred combinations of resins that provide a viscosity of 100 Pa or more include: A combination in which the main resin constituting the adhesive layer is a thermoplastic polyimide and the main resin constituting the inorganic filler-containing resin layer is a liquid crystal polymer; A combination in which the main resin constituting the adhesive layer is a thermoplastic polyimide and the main resin constituting the inorganic filler-containing resin layer is a polyphenylene sulfide; A combination in which the main resin constituting the adhesive layer is a thermoplastic polyimide and the main resin constituting the inorganic filler-containing resin layer is a polyether ether ketone; A combination in which the main resin constituting the adhesive layer is a thermoplastic polyimide and the main resin constituting the inorganic filler-containing resin layer is a syndiotactic polystyrene; A combination in which the main resin constituting the adhesive layer is polyphenylene ether and the main resin constituting the inorganic filler-containing resin layer is a liquid crystal polymer; A combination in which the main resin constituting the adhesive layer is polyphenylene ether and the main resin constituting the inorganic filler-containing resin layer is polyphenylene sulfide; A combination in which the main resin constituting the adhesive layer is polyphenylene ether and the main resin constituting the inorganic filler-containing resin layer is polyether ether ketone; A combination in which the main resin constituting the adhesive layer is polyphenylene ether and the main resin constituting the inorganic filler-containing resin layer is syndiotactic polystyrene; Some examples include:

[0028] Condition D): When the main resin constituting the adhesive layer is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer is an amorphous resin, the storage modulus E' of the adhesive layer at the glass transition temperature Tg2 of the inorganic filler-containing resin layer is 1×10 6 Must be Pa or higher. The storage modulus E' of the adhesive layer at the glass transition temperature Tg2 is 1×10 6 By having a storage modulus E' of 1 x 10 Pa or more, it is possible to effectively prevent the adhesive layer from flowing out or having uneven thickness when performing thermocompression bonding at a temperature above the glass transition point Tg2 to eliminate voids in the inorganic filler-containing resin layer. Therefore, in a metal-clad laminate, it is possible to reduce voids in the inorganic filler-containing resin layer and ensure adhesion to the metal foil while preventing the adhesive layer from flowing out or having uneven thickness. In contrast, when the storage modulus E' of the adhesive layer at the glass transition point Tg2 is 1 x 10 6 If it is less than Pa, there is a risk that the adhesive layer will flow out or have uneven thickness during thermocompression bonding at a temperature exceeding the glass transition point Tg2.

[0029] The storage modulus E' at the glass transition temperature Tg2 of the inorganic filler-containing resin layer is 1×10 6 Preferable combinations of amorphous resins having a viscosity of 1 Pa or more include, for example, A combination in which the main resin constituting the adhesive layer is a thermoplastic polyimide and the main resin constituting the inorganic filler-containing resin layer is a polyphenylene ether; A combination in which the main resin constituting the adhesive layer is polyphenylene ether and the main resin constituting the inorganic filler-containing resin layer is thermoplastic polyimide; A combination in which the main resin constituting the adhesive layer is a thermoplastic polyimide and the main resin constituting the inorganic filler-containing resin layer is a cycloolefin polymer; A combination in which the main resin constituting the adhesive layer is polyphenylene ether and the main resin constituting the inorganic filler-containing resin layer is a cycloolefin polymer; Some examples include:

[0030] Next, each layer constituting the metal-clad laminate of the present invention will be described.

[0031] (metal layer) The material of the metal layer is not particularly limited, but examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferable. The material of the wiring layer in the circuit board of this embodiment described later is the same as that of the metal layer.

[0032] The thickness of the metal layer is not particularly limited, but when a metal foil such as copper foil is used, it is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the metal foil is preferably 5 μm. When copper foil is used, it may be rolled copper foil or electrolytic copper foil. In addition, commercially available copper foil may be used as the copper foil.

[0033] The surface roughness of the metal layer is not particularly limited, but from the viewpoint of ensuring adhesion to the adhesive layer while reducing conductor loss, it is preferable for the metal layer to have a roughened surface with a ten-point mean roughness (Rzjis) in the range of 0.3 to 1.5. Note that the lower the surface roughness of the metal layer, the greater the effect of providing the adhesive layer, so it is more preferable for the ten-point mean roughness (Rzjis) to be in the range of 0.3 to 1.0. The metal foil may be subjected to a surface treatment using, for example, siding, aluminum alcoholate, aluminum chelate, a silane coupling agent, or the like, for the purpose of, for example, rust prevention or improving adhesive strength.

[0034] (Adhesive layer) The "main resin" constituting the adhesive layer may be the crystalline resin or non-crystalline resin exemplified above. The adhesive layer may contain resins other than the main resin, organic or inorganic fillers, etc., within the scope of the invention.

[0035] (Inorganic filler-containing resin layer) The inorganic filler-containing resin layer contains a matrix resin and an inorganic filler dispersed in the matrix resin. The matrix resin constituting the inorganic filler-containing resin layer may be a single resin, or may be a mixture (polymer blend) of two or more resins. When the matrix resin is a mixture of two or more resins, they may be in a compatible state or in a different separated state.

[0036] The main component of the matrix resin, i.e., the "main resin" constituting the inorganic filler-containing resin layer, may be the crystalline resin or non-crystalline resin exemplified above. The "main resin" constituting the inorganic filler-containing resin layer is provided in a powder state for forming the inorganic filler-containing resin layer, and is melted by thermocompression bonding to become the inorganic filler-containing resin layer.

[0037] In addition, the matrix resin may contain, for example, a low elasticity resin as a resin other than the main resin, within a range that does not impair the effects of the invention. The term "low elasticity resin" means a resin that, when made into a film, has a storage modulus of 2500 MPa or less at 50°C and a maximum storage modulus of 800 MPa or less in a temperature range from 180°C to 260°C. Here, "when made into a film" means that the low elasticity resin is made into a film state by itself. Since the low elasticity resin has a sufficiently low storage modulus at 50°C and in a temperature range from 180°C to 260°C in a film state, the inorganic filler-containing resin layer containing the main resin and the inorganic filler exhibits excellent binding action and stress relaxation action. From this viewpoint, it is preferable to use a resin whose storage modulus at 50°C is preferably 2000 MPa or less and whose maximum storage modulus in a temperature range from 180°C to 260°C is preferably 500 MPa or less, more preferably 100 MPa or less.

[0038] The low elasticity resin is a component having a binding action and a stress relaxation action. By blending the low elasticity resin, it is possible to prevent the occurrence of powder falling and cracking of the coating film (dispersion composition layer described later) when forming the inorganic filler-containing resin layer. In particular, in a coating film having a thickness of 50 μm or more, the expansion and contraction stress difference in the thickness direction is likely to become large, so by blending the low elasticity resin, the effect of preventing cracking is greatly exhibited. In order to effectively exhibit such binding action and stress relaxation action, it is preferable that the low elasticity resin is dissolved in an organic solvent and contained in the dispersion composition (described later) used to form the inorganic filler-containing resin layer. The low elasticity resin may be directly soluble in the organic solvent used in the dispersion composition, or may be dissolved once in any organic solvent other than the organic solvent used in the dispersion composition and then mixed with the organic solvent used in the dispersion composition.

[0039] Examples of low elasticity resins include polyimide, polyamide, epoxy resin, phenoxy resin, acrylic resin, polyurethane, styrene resin, polyester, phenol resin, polysulfone, polyethersulfone, polyphenylene sulfide, polyethylene, polypropylene, silicone resin, polyetherketone, polyvinyl alcohol, polyvinyl butyral, styrene-maleimide copolymer, maleimide-vinyl compound copolymer, (meth)acrylic copolymer, benzoxazine resin, bismaleimide resin, and cyanate ester resin. Among these, resins that satisfy the above storage modulus can be selected or designed to satisfy the above storage modulus and used. Two or more of these low elasticity resins can be used in combination. Among the above low elasticity resins, thermoplastic polyimide, silicone resin, etc. are preferred from the viewpoint of having both low elasticity and heat resistance, and polyimide using an aliphatic diamine as a raw material is more preferred.

[0040] In addition, the weight average molecular weight of the low elasticity resin is not particularly limited, but from the viewpoint of solubility in a solvent, the number average molecular weight is preferably within the range of 10,000 to 300,000, and more preferably within the range of 10,000 to 100,000. In addition, the low elasticity resin is preferably soluble in a polar organic solvent such as ethyl acetate, methyl ethyl ketone, or N,N-dimethylacetamide.

[0041] In addition, the total amount of the low elasticity resin in the dispersion composition is 3.5 parts by weight or more, preferably 3.5 to 14.0 parts by weight, more preferably 4.5 to 11.5 parts by weight, based on 100 parts by weight of the main resin powder and inorganic filler in the inorganic filler-containing resin layer, from the viewpoint of effectively exerting the binding action and stress relaxation action. If the total amount of the low elasticity resin is less than 3.5 parts by weight based on 100 parts by weight of the main resin powder and inorganic filler in the inorganic filler-containing resin layer, the effect of preventing powder falling and cracking of the coating film cannot be sufficiently obtained. On the other hand, if the total amount of the low elasticity resin exceeds 14.0 parts by weight based on 100 parts by weight of the main resin powder and inorganic filler in the inorganic filler-containing resin layer, there is a concern that it may be difficult to control the CTE or reduce the dielectric loss tangent.

[0042] The type of inorganic filler is not particularly limited, but from the viewpoint of reducing the thermal expansion coefficient of the inorganic filler-containing resin layer, for example, silicon dioxide (silica), aluminum oxide (alumina), magnesium oxide (magnesia), beryllium oxide, niobium oxide, titanium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, magnesium fluoride, potassium silicofluoride, talc, glass, barium titanate, etc. are preferable. These may be used in combination of two or more. Among these, silicon dioxide (silica), aluminum oxide, boron nitride, glass, etc. are more preferable as those having a low thermal expansion coefficient.

[0043] Average particle size of inorganic filler (D 50 There is no particular restriction on the specific surface area, but it is preferably in the range of 0.05 to 50 μm, and more preferably in the range of 0.1 to 20 μm, from the viewpoint of preventing deterioration of the dielectric loss tangent, while taking into consideration the ratio to the thickness of the insulating layer when used in a circuit board and from the viewpoint of ensuring the drilling processability of the insulating layer. 2 / g, preferably 0.1 to 10 m 2The average particle size of the inorganic filler can be determined, for example, by measuring the particle size distribution of the powder particles by a laser diffraction / scattering method, calculating a cumulative curve with the total volume of the powder particles set to 100%, and measuring the particle size at the point on the cumulative curve where the cumulative volume is 50%, and the specific surface area can be measured by the BET method.

[0044] The shape of the inorganic filler is not particularly limited, but from the viewpoint of reducing the difference in thermal expansion coefficient between the thickness direction and the surface direction, for example, a spherical shape, a crushed spherical shape, etc. Also, the inorganic filler may be hollow.

[0045] The inorganic filler is preferably surface-treated with a coupling agent, etc. Examples of the coupling agent used for the surface treatment include 3-aminopropylethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropylethoxysilane, 3-isocyanatopropylethoxysilane, and hexamethyldisilazane.

[0046] The dispersion composition used to form the inorganic filler-containing resin layer preferably contains the above-mentioned low elasticity resin, dispersant, etc. The type of dispersant is not particularly limited as long as it can disperse the powder of the main resin constituting the inorganic filler-containing resin layer and the inorganic filler.

[0047] From the viewpoint of lowering the dielectric tangent and making it compatible with high-frequency signal transmission, the weight proportion of the main resin in the inorganic filler-containing resin layer is preferably within the range of 10 to 40 parts by weight, and more preferably within the range of 15 to 35 parts by weight, per 100 parts by weight of the total solid content of the inorganic filler-containing resin layer. In addition, the weight ratio of the inorganic filler is preferably within the range of 60 to 90 parts by weight, more preferably within the range of 70 to 85 parts by weight, relative to 100 parts by weight of the total solid content of the inorganic filler-containing resin layer, from the viewpoint of lowering the coefficient of thermal expansion (CTE) and ensuring dimensional stability when applied to a circuit board. In addition, from another viewpoint, the content ratio of the inorganic filler in the inorganic filler-containing resin layer is preferably within the range of, for example, 45 to 75 volume % relative to the total solid content of the inorganic filler-containing resin layer, more preferably within the range of 60 to 75 volume %, in order to suppress the coefficient of thermal expansion (CTE) of the inorganic filler-containing resin layer and the insulating layer as a whole. In particular, by containing the inorganic filler at a high concentration of 60 volume % or more, voids are easily generated in the coating film, and the effect of the invention is easily exhibited. The content of the dispersant in the dispersion composition used to form the inorganic filler-containing resin layer is preferably, for example, 10 parts by weight or less, and more preferably within the range of 0.5 to 5 parts by weight, as the dispersant active ingredient, per 100 parts by weight of the total solid content of the inorganic filler-containing resin layer.

[0048] The coefficient of thermal expansion (CTE) of the inorganic filler-containing resin layer is preferably 60 ppm / K or less, and more preferably in the range of 10 ppm / K to 30 ppm / K. If the coefficient of thermal expansion (CTE) of the inorganic filler-containing resin layer exceeds 60 ppm / K, the dimensional stability of the metal-clad laminate is not guaranteed, and problems such as misalignment of wiring positions may occur after circuit processing.

[0049] The inorganic filler-containing resin layer preferably has a dielectric loss tangent at 20 GHz measured by a split post dielectric resonator (SPDR resonator) of less than 0.0025, more preferably less than 0.0020, after being left for 24 hours under conditions of temperature: 24 to 26°C and humidity: 45 to 55%, and preferably has a relative dielectric constant measured under the same conditions of less than 4.0, more preferably less than 3.5, and even more preferably less than 3.0. If the dielectric tangent and the relative dielectric constant exceed the above values, when the material is applied to a circuit board, this leads to an increase in dielectric loss, and is likely to cause problems such as loss of electrical signals on the transmission path of high-frequency signals in the GHz band (e.g., 1 to 80 GHz).

[0050] FIG. 1 shows a cross-sectional structure of a metal-clad laminate 100 according to a preferred embodiment of the present invention. The metal-clad laminate 100 has a structure in which a metal layer 10A / an adhesive layer 20A / an inorganic filler-containing resin layer 30 / an adhesive layer 20B / a metal layer 10B are laminated in this order. The metal layer 10A and the metal layer 10B are located on the outermost sides, respectively, and the adhesive layer 20A and the adhesive layer 20B are disposed on the inner side of them, and further, an inorganic filler-containing resin layer 30 is interposed between the adhesive layer 20A and the adhesive layer 20B. The metal-clad laminate is not limited to the layer structure shown in FIG. 1, and may have any layer, for example.

[0051] As described above, the metal-clad laminate 100 has the following features: a) when the main resin constituting the adhesive layer 20A and the adhesive layer 20B is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer 30 is a crystalline resin, the melting point Tm1 of the main resin constituting the adhesive layer 20A and the adhesive layer 20B is higher than the melting point Tm2 of the inorganic filler-containing resin layer 30; b) when the main resin constituting the adhesive layer 20A and the adhesive layer 20B is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer 30 is an amorphous resin, the melting point Tm1 of the main resin constituting the adhesive layer 20A and the adhesive layer 20B is higher than the glass transition point Tg2 of the inorganic filler-containing resin layer 30; c) When the main resin constituting the adhesive layer 20A and the adhesive layer 20B is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer 30 is a crystalline resin, the storage modulus E' of the adhesive layer 20A and the adhesive layer 20B at the melting point Tm2 of the inorganic filler-containing resin layer 30 is 1×10 6 Pa or more; d) When the main resin constituting the adhesive layer 20A and the adhesive layer 20B is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer 30 is an amorphous resin, the storage modulus E′ of the adhesive layer 20A and the adhesive layer 20B at the glass transition temperature Tg2 of the inorganic filler-containing resin layer 30 is 1×10 6 Pa or more; meets one of the following conditions.

[0052] In the metal-clad laminate 100, the adhesive layer 20A and the adhesive layer 20B may have the same or different configurations, but preferably have the same configuration. When the adhesive layer 20A and the adhesive layer 20B have different configurations, it is preferable that each of them satisfies any one of the above conditions a) to d).

[0053] In the metal-clad laminate 100, the thicknesses of the adhesive layers 20A and 20B are each preferably within the range of 1 to 20 μm, and more preferably within the range of 2 to 10 μm. If the thickness is less than 1 μm, sufficient adhesion to the metal layers 10A and 10B may not be obtained, and if it exceeds 20 μm, the dimensional stability of the entire metal-clad laminate 100 may be impaired and the dielectric properties may be deteriorated. The thicknesses of the adhesive layers 20A and 20B may be the same or different, but are preferably the same.

[0054] In the metal-clad laminate 100, the thickness of the inorganic filler-containing resin layer 30 is preferably within a range of 60 to 150 μm, and more preferably within a range of 80 to 130 μm. If the thickness is less than 60 μm, it may be difficult to suppress transmission loss when the metal-clad laminate 100 is used as a circuit board, which may make it difficult to support high-frequency signal transmission, and if the thickness exceeds 150 μm, handling during production may be difficult.

[0055] In the metal-clad laminate 100, the total thickness T of the adhesive layer 20A, the adhesive layer 20B, and the inorganic filler-containing resin layer 30 is AD (i.e., the total thickness of adhesive layer 20A and adhesive layer 20B) ratio [(T ADThe ratio [(T / T)×100] is preferably in the range of 1 to 25%, and more preferably in the range of 2 to 20%. AD If the ratio of [(x,y) / T)×100] is less than 1%, sufficient adhesion to metal layers 10A, 10B may not be obtained, and if it exceeds 25%, the dimensional stability of the entire metal-clad laminate 100 may be impaired and the dielectric properties may be deteriorated.

[0056] The coefficient of thermal expansion (CTE) of the entire insulating layer including the adhesive layer 20A, the adhesive layer 20B, and the inorganic filler-containing resin layer 30 is preferably 60 ppm / K or less, and more preferably within the range of 10 ppm / K to 30 ppm / K. If the coefficient of thermal expansion (CTE) of the entire insulating layer exceeds 60 ppm / K, the dimensional stability of the metal-clad laminate is not guaranteed, and problems such as misalignment of wiring positions may occur after circuit processing.

[0057] In addition, the dielectric properties of the entire insulating layer including the adhesive layer 20A and the adhesive layer 20B and the inorganic filler-containing resin layer 30 are preferably less than 0.0025, more preferably less than 0.0020, in terms of the dielectric tangent at 20 GHz measured by a split post dielectric resonator (SPDR resonator) after leaving it for 24 hours under conditions of temperature: 24 to 26°C and humidity: 45 to 55%. In addition, the relative dielectric constant measured under the same conditions is preferably 4.0 or less, more preferably 3.5 or less, and even more preferably 3.0 or less. If the dielectric tangent and relative dielectric constant exceed the above values, this leads to an increase in dielectric loss when applied to a circuit board, and is likely to cause inconveniences such as loss of electrical signals on the transmission path of high-frequency signals in the GHz band (for example, 1 to 80 GHz).

[0058] [Metal-clad laminate manufacturing method] The metal-clad laminate 100 is preferably produced, for example, according to the following method 1 or method 2.

[0059] (Method 1) 2, a laminate in which a metal layer 10A and an adhesive layer 20A are laminated, and a laminate in which a metal layer 10B and an adhesive layer 20B are laminated are prepared. These are referred to as a first laminate 40.

[0060] Next, the dispersion composition that will become the inorganic filler-containing resin layer 30 is applied to a predetermined thickness on each of the adhesive layers 20A and 20B of the first laminate 40, and after drying, is heated to a temperature equal to or higher than the melting temperature of the main resin (in methods 1 and 2, this means the main resin that constitutes the inorganic filler-containing resin layer 30; the same applies below), thereby forming the dispersion composition layer 31 as shown in Fig. 3, and producing two second laminates 50. At this stage, the dispersion composition layer 31 of the second laminate 50 contains voids.

[0061] Next, as shown in FIG. 4, the two second laminates 50 are laminated with the dispersion composition layers 31 facing each other and thermocompression bonded. The main resin in the dispersion composition layer 31 is melted by thermocompression and flows into the voids in the layer, and then cooled and solidified to eliminate the voids and form the inorganic filler-containing resin layer 30. The thermocompression temperature may be equal to or higher than the melting point Tm2 or glass transition point Tg2 of the inorganic filler-containing resin layer 30, and the upper limit can be appropriately determined depending on the type of resin. For example, it is preferable to set the temperature to be higher than the melting point Tm2 or glass transition point Tg2 within the range of 10°C to 80°C. The pressure during thermocompression can be appropriately determined depending on the type of resin, but is preferably set within the range of 2 to 20 MPa. In this manner, a metal-clad laminate 100 can be produced having a layer structure in which metal layer 10A / adhesive layer 20A / inorganic filler-containing resin layer 30 (which is a layer formed by bonding two dispersion composition layers 31 together) / adhesive layer 20B / metal layer 10B are laminated in this order, as shown in FIG. 1.

[0062] (Method 2) First, a laminate in which the metal layer 10A and the adhesive layer 20A are laminated, and a laminate in which the metal layer 10B and the adhesive layer 20B are laminated are prepared, and these are designated as a first laminate 40 (see FIG. 2).

[0063] Next, the dispersion composition that will become the inorganic filler-containing resin layer 30 is applied to a predetermined thickness on the adhesive layer 20A of the first laminate, and after drying, the main resin is heated to a melting temperature or higher to form the dispersion composition layer 31, thereby forming the second laminate 50 (see FIG. 3). However, in method 2, the thickness of the dispersion composition layer 31 is set to be about twice as thick as in method 1. At this stage, the dispersion composition layer 31 of the second laminate 50 contains voids.

[0064] Next, as shown in FIG. 5, the second laminate 50 and the first laminate 40 are thermocompression bonded so that the dispersion composition layer 31 of the second laminate 50 and the adhesive layer 20B of the first laminate 40 face each other. By thermocompression bonding, the main resin in the dispersion composition layer 31 is melted and flows into the voids in the layer, and then cooled and solidified to eliminate the voids, forming the inorganic filler-containing resin layer 30. The thermocompression bonding conditions can be the same as those in method 1. In this way, a metal-clad laminate 100 having a layer structure in which the metal layer 10A / adhesive layer 20A / inorganic filler-containing resin layer 30 / adhesive layer 20B / metal layer 10B are laminated in this order can be manufactured.

[0065] The dispersion composition used in methods 1 and 2 preferably contains a powder of a main resin and an inorganic filler, and further contains, as necessary, a low-elasticity resin, a dispersant, an organic solvent, etc. The weight ratio of the powder of the main resin in the dispersion composition is preferably within a range of 10 to 40 parts by weight, more preferably within a range of 15 to 35 parts by weight, relative to 100 parts by weight of the total solid content in the dispersion composition, from the viewpoint of lowering the dielectric tangent when made into a film and making it compatible with high-frequency signal transmission.

[0066] In addition, the weight proportion of the inorganic filler in the dispersion composition is preferably within the range of 60 to 90 parts by weight, and more preferably within the range of 70 to 85 parts by weight, per 100 parts by weight of the total solid content in the dispersion composition, from the viewpoints of reducing the coefficient of thermal expansion (CTE) when made into a film and ensuring dimensional stability when applied to a circuit board. When a low elasticity resin is blended, the content is, for example, preferably 15 parts by weight or less, and more preferably within the range of 3 to 7 parts by weight, relative to 100 parts by weight of the total solid content of the dispersion composition.

[0067] In addition, when a dispersant is contained, the content is preferably, for example, 10 parts by weight or less as a dispersant active ingredient relative to 100 parts by weight of the total solid content of the dispersion composition, and more preferably in the range of 0.5 to 5 parts by weight. In addition, when an organic solvent is contained, in order to obtain good dispersibility and good coatability, the total amount of the main resin powder and the inorganic filler is preferably in the range of 40 to 80% by weight of the entire composition, and more preferably in the range of 50 to 70% by weight. The solid content in the dispersion composition means the total of the components excluding the solvent.

[0068] In addition, the viscosity of the dispersion composition is not particularly limited, but for example, when the purpose is to coat a thick film of 30 μm or more, it is preferably in the range of 500 to 50,000 cP, more preferably in the range of 500 to 30,000 cP. If the viscosity is less than 500 cP, the fluidity becomes too high when the dispersion composition is cast, making it difficult to form a thick coating film. In particular, it becomes impossible to form a relatively thick coating film in the range of 30 to 150 μm for high frequency transmission applications. In addition, if the viscosity is less than 500 cP, sedimentation or aggregation of solids may occur. On the other hand, if the viscosity of the dispersion composition exceeds 50,000 cP, the viscosity is too high and it becomes difficult to form a coating film by casting. The viscosity of the dispersion composition can be measured at a temperature of 25°C using an E-type viscometer.

[0069] The first laminate 40 used in methods 1 and 2 can be produced, for example, by applying a solution of an adhesive composition for forming the adhesive layers 20A and 20B onto a metal foil that will become the metal layers 10A and 10B, and drying the applied solution.

[0070] In methods 1 and 2, the method for applying the dispersion composition or adhesive composition solution onto the metal foil or adhesive layer 20A, 20B is not particularly limited, and it is possible to apply it using, for example, a coater such as a comma, die, knife, or lip coater.

[0071] The metal-clad laminate 100 of the present embodiment obtained as described above can be used to manufacture a circuit board such as a single-sided circuit board or a double-sided circuit board by wiring and circuit processing, such as by etching the metal layer 10A and / or the metal layer 10B.

[0072] [Circuit board] The metal-clad laminate 100 of the present embodiment is useful mainly as a circuit board material for FPCs, rigid-flex circuit boards, rigid boards, etc. For example, a circuit board such as an FPC according to one embodiment of the present invention can be manufactured by processing one or both of the two metal layers 10A, 10B of the metal-clad laminate 100 shown in Fig. 1 into a pattern by a conventional method to form a wiring layer. EXAMPLES

[0073] The features of the present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to the examples. In the following examples, various measurements and evaluations are as follows, unless otherwise specified.

[0074] [Peel strength measurement] Only one of the copper foil surfaces of the double-sided copper-clad laminate was circuitized in the resin coating direction at 10 mm intervals to a width of 1 mm, and the laminate was cut to a width of 8 cm and length of 4 cm to prepare a measurement sample. The peel strength was measured using a Tensilon tester (manufactured by Toyo Seiki Seisakusho, product name: Strograph VE-1D) by fixing the unprocessed copper foil surface of the cut measurement sample to an aluminum plate with double-sided tape, peeling the circuit-processed copper foil in the 180° direction at a speed of 50 mm / min, and determining the median strength when 10 mm was peeled off.

[0075] [Measurement of resin outflow from adhesive layer] The ends of the prepared double-sided copper-clad laminate were visually inspected for any resin outflow, and only when outflow was confirmed was the area with the largest amount of outflow measured using an optical microscope, and the amount of outflowed resin was calculated.

[0076] [Measurement of resin layer thickness] For the double-sided copper-clad laminate thus produced, a cross-section polisher was used to produce a precise polished cross-section perpendicular to the double-sided copper-clad laminate, and the thickness of each resin layer was measured for this cross-section using a scanning electron microscope (SEM).

[0077] [Void evaluation] A cross-section polisher was used to precisely polish the cross section of the double-sided copper-clad laminate in the perpendicular direction to the laminate, and 5 random images of the inorganic filler-containing resin layer were taken at 2000x magnification using a scanning electron microscope (SEM). Next, the void and other parts of the images were binarized to calculate the volume fraction of the voids in the inorganic filler-containing resin layer. Porosity (vol.%) = Volume of voids in the image / Volume of inorganic filler-containing resin layer in the image

[0078] [Measurement of coefficient of thermal expansion (CTE)] The resin film was cut to a size of 3 mm in the coating width direction and 20 mm in the coating direction and set in a thermomechanical analyzer (Hitachi High-Technologies Corporation, product name: TMA / SS7100). At this time, the distance between the device jigs (effective measurement length) was 15 mm. Next, the temperature was raised from 30°C to 260°C at a constant heating rate while applying a load of 5.0 g, and then the temperature was held for 10 minutes, and then cooled at a rate of 5°C / min, and the average thermal expansion coefficient (thermal expansion coefficient) from 250°C to 100°C was obtained.

[0079] [Measurement of dielectric constant and dielectric tangent] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin film at a frequency of 20 GHz were measured using a vector network analyzer (manufactured by Agilent, product name: E8363C) and a split post dielectric resonator (SPDR resonator). The Df after humidity control was measured after the resin film used for the measurement was left to stand for 24 hours under conditions of temperature: 24 to 26° C. and humidity: 45 to 55%.

[0080] [Measurement of copper foil surface roughness] The surface roughness of the copper foil was measured in tapping mode using an AFM (manufactured by Bruker AXS, product name: Dimension Icon type SPM) and a probe (manufactured by Bruker AXS, product name: TESPA (NCHV), tip curvature radius 10 nm, spring constant 42 N / m) over an area of ​​80 μm × 80 μm on the copper foil surface, and the ten-point average roughness (Rzjis) was calculated.

[0081] [Measurement of melting point of crystalline resin and storage modulus and glass transition point of amorphous resin at 300℃ and 350℃] The melting point of the crystalline resin was determined by measuring a film of 5 mm × 70 mm using a dynamic viscoelasticity measuring device (DMA: manufactured by TA Instruments, product name: RSA G2) at a heating rate of 4°C / min from 30°C to 400°C and a frequency of 1 Hz, and was determined as the temperature at which the change in elastic modulus (tan δ) was maximum. The storage modulus of the amorphous resin was measured using a dynamic viscoelasticity measuring device in the same manner as for the melting point of the crystalline resin, and the storage modulus at each temperature was confirmed. Furthermore, the glass transition point (Tg) was calculated from the change in the elastic modulus (tan δ). In addition, to determine whether a resin is crystalline or amorphous, when a film was measured using a differential scanning calorimeter, if there was a clear endothermic peak associated with melting near the temperature at which tan δ obtained by dynamic viscoelasticity measurement was maximum, the resin was defined as crystalline, and if there was a baseline shift due to glass transition, the resin was defined as amorphous.

[0082] The compounds used in the synthesis examples and dispersion composition preparation examples are shown below. LCP powder (1): XYDAR LF-31P, liquid crystal resin powder made by ENEOS, average particle size: 2~3μm PPE powder (1): S203A, Asahi Kasei polyphenylene ether powder, average particle size: 7-8 μm Fluorine-based resin powder (1): Fluon+ (Fluon is a registered trademark) EA-2000PW10, fluorine-based resin powder manufactured by AGC, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, average particle size: 2 to 3 μm Silica filler (1): SC70-2: Amorphous silica filler manufactured by Nippon Steel Chemical & Material Co., Ltd., average particle size (D50); 11.7 μm, specific surface area 1.1 m2 / g, treated with 0.12% by weight of hexamethyldisilazane. Dispersant (1): Futergent 710FL: Neos nonionic fluorine-containing dispersant (dispersant component 50% by weight, ethyl acetate 50% by weight) BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride PMDA: Pyromellitic dianhydride m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl TPE-R: 1,3-bis(4-aminophenoxy)benzene DMAc: N,N-dimethylacetamide THF: tetrahydrofuran NMP: N-methyl-2-pyrrolidone Xylene BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride BAFL: 9,9-bis(4-aminophenyl)fluorene DDA: aliphatic diamine having 36 carbon atoms (manufactured by Croda Japan Co., Ltd., product name: PRIAMINE 1074, amine value: 205 mg KOH / g, mixture of dimer diamines having cyclic and chain structures, dimer component content: 95% by weight or more) Copper foil (1): CF-T9DA-SV-12: Manufactured by Fukuda Metal Foil and Powder Industries Co., Ltd., ten-point average roughness (Rzjis); 0.9 μm

[0083] (Synthesis Example 1) <Preparation of Soluble Polyimide Varnish (1)> A 500mL four-neck flask equipped with a nitrogen inlet tube, a stirrer, a thermocouple, a Dean-Stark trap, and a cooling tube was charged with 38.45g of BTDA (0.119 mol), 31.50g of DDA (0.059 mol), 20.47g of BAFL (0.059 mol), 127g of NMP, and 84g of xylene, and mixed at 40°C for 30 minutes to prepare a polyamic acid solution. The polyamic acid solution was heated to 180°C, heated and stirred for 4 hours, and the distilled water and xylene were removed from the system. Thereafter, the solution was cooled to 100°C, 51g of xylene was added and stirred, and the solution was further cooled to 30°C to prepare a soluble polyimide varnish (1) (solid content: 31.0% by weight, weight average molecular weight: 58,400) in which imidization was completed. Soluble polyimide varnish (1) was applied to a substrate, dried, and then peeled off to obtain a polyimide film. The storage modulus of the polyimide film was measured, and the storage modulus at 50° C. was 2.0 GPa, and the maximum storage modulus in the temperature range from 180° C. to 260° C. was 3.0 MPa. The dielectric properties were: relative permittivity 2.8, and dielectric dissipation factor 0.0023.

[0084] (Synthesis Example 2) <Preparation of polyamic acid varnish (1)> Under a nitrogen stream, 2.7701 g of m-TB (0. 0.01305 mol) and 15.2580 g of TPE-R (0.05219 mol) and polymerization DMAc was added in an amount such that the final solid concentration would be 12% by weight, and the mixture was stirred at room temperature to dissolve. Next, 13.6386 g of BPDA (0.04636 moles) and 4.3333 g of PMD After adding A (0.01987 mol), the polymerization reaction was carried out by stirring at room temperature for 3 hours. Polyamic acid varnish (1) was obtained. The solution viscosity of polyamic acid varnish (1) was 1600 cP.

[0085] (Dispersion Composition Preparation Example 1-1) In a 310 ml polypropylene container, 100.0 g of fluororesin powder (1), 10.0 g of dispersant (1) (5.0 g of dispersant component), and 90 g of DMAc were added to prepare two samples. Next, the two samples were set in a rotary mixer [Shashin Kagaku Co., Ltd. SK-350G] and stirred for 4 minutes under conditions of a revolution of 1060 rpm and a rotation of 1060 rpm, to obtain a dispersion composition 1-1 with a viscosity of 430 cP when measured at 100 rpm.

[0086] (Dispersion Composition Preparation Example 1-2) Two samples were prepared by adding 9.9 g of LCP powder (1), 51.8 g of silica filler (1), and 27.6 g of THF to a 310 ml polypropylene container. Next, the two samples were set in a rotary mixer [Shashin Kagaku Co., Ltd. SK-350G] and stirred for 2 minutes under the conditions of a revolution of 1060 rpm and a rotation of 1060 rpm. Then, 10.7 g of soluble polyimide varnish (1) was added to each container and further stirred for 2 minutes under the stirring conditions to obtain dispersion composition 1-2.

[0087] (Dispersion Composition Preparation Example 1-3) Two samples were prepared by adding 13.9 g of LCP powder (1), 51.1 g of silica filler (1), and 35.0 g of THF to a 310 ml polypropylene container. The two samples were then set in a rotary mixer [SK-350G, manufactured by Photo Chemical Co., Ltd.] and stirred for 4 minutes under conditions of a revolution of 1060 rpm and a rotation of 1060 rpm to obtain a dispersion composition 1-3.

[0088] (Dispersion Composition Preparation Example 1-4) Two samples were prepared by adding 6.6 g of PPE powder (1), 45.5 g of silica filler (1), and 38.5 g of THF to a 310 ml polypropylene container. Next, the two samples were set in a rotary mixer [Shashin Kagaku Co., Ltd. SK-350G] and stirred for 2 minutes under conditions of 1060 rpm revolution and 1060 rpm rotation, and then 9.4 g of soluble polyimide varnish (1) was added to each container and further stirred for 2 minutes under the above stirring conditions to obtain dispersion composition 1-4.

[0089] (Dispersion Composition Preparation Example 1-5) Two samples were prepared by adding 10.2 g of PPE powder (1), 30.2 g of silica filler (1), and 45.0 g of THF to a 310 ml polypropylene container. Next, the two samples were set in a rotary mixer [Shashin Kagaku Co., Ltd. SK-350G] and stirred for 2 minutes under the conditions of a revolution of 1060 rpm and a rotation of 1060 rpm. Then, 14.6 g of soluble polyimide varnish (1) was added to each container and further stirred for 2 minutes under the stirring conditions to obtain dispersion composition 1-5.

[0090] (Production Example 1) Dispersion composition 1-1 was applied onto copper foil (1), and then dried using a hot air oven at 80° C. for 1 minute and at 120° C. for 3 minutes. Next, using a hot air oven in a nitrogen atmosphere (oxygen concentration 0.1% by volume or less), the temperature was increased from 40° C. to 240° C. at 10° C. / min, and from 240° C. to 360° C. at 5° C. / min, and then the plate was held at 360° C. for 5 minutes, followed by cooling to 40° C. to obtain a single-sided copper-clad laminate 1.

[0091] Next, two single-sided copper-clad laminates 1 were prepared, and the resin surfaces were placed together in a batch press machine, after which they were heated in a vacuum from 40°C to 320°C over 50 minutes, and as soon as the temperature reached 320°C, a pressure of 2 MPa was applied. After that, the laminate was held at 320°C for 5 minutes, and then cooled to 40°C over 50 minutes, and as soon as the temperature reached 40°C, the pressure was released, yielding a double-sided copper-clad laminate 1 with a dielectric layer thickness of 100 μm.

[0092] Next, the copper foil of the double-sided copper-clad laminate 1 was etched away using an aqueous solution of ferric chloride to prepare a fluororesin film 1. The fluororesin film 1 had a CTE of 240 ppm / K, a relative dielectric constant of 2.1, a dielectric loss tangent of 0.001, and a melting point (Tm) of 305°C.

[0093] (Production Example 2) Dispersion composition 1-2 was applied onto copper foil (1), and then dried using a hot air oven at 80° C. for 1 minute and at 120° C. for 3 minutes. Next, using a hot air oven in a nitrogen atmosphere (oxygen concentration 0.1% by volume or less), the temperature was increased from 40° C. to 240° C. at 10° C. / min, and from 240° C. to 360° C. at 5° C. / min, and the temperature was held at 360° C. for 5 minutes, followed by cooling to 40° C. to obtain a single-sided copper-clad laminate 2.

[0094] Next, two single-sided copper-clad laminates 2 were prepared, and the resin surfaces were placed together in a batch press machine, after which they were heated in a vacuum from 40°C to 360°C over 50 minutes, and as soon as the temperature reached 360°C, a pressure of 12 MPa was applied. After that, the laminates were held at 360°C for 5 minutes, and then cooled to 40°C over 50 minutes. As soon as the temperature reached 40°C, the pressure was released, yielding a double-sided copper-clad laminate 2 with a dielectric layer thickness of 100 μm.

[0095] Subsequently, the copper foil of the double-sided copper-clad laminate 2 was etched away using an aqueous solution of ferric chloride to prepare a filler-containing resin film 1. The filler-containing resin film 1 had a CTE of 26 ppm / K, a relative dielectric constant of 3.3, a dielectric tangent of 0.0008, and a melting point (Tm) of 321°C.

[0096] (Production Example 3) Dispersion composition 1-3 was applied onto copper foil (1), and then dried using a hot air oven at 80°C for 1 minute and 120°C for 3 minutes. Next, using a hot air oven in a nitrogen atmosphere (oxygen concentration 0.1% by volume or less), the temperature was increased from 40°C to 240°C at 10°C / min, and from 240°C to 360°C at 5°C / min, and the plate was held at 360°C for 5 minutes, and then cooled to 40°C. A single-sided copper-clad laminate 3 was obtained by nitrogen heat treatment. At this time, cracks were observed on part of the coating surface.

[0097] Next, two single-sided copper-clad laminates 3 were prepared, and the resin surfaces were placed together in a batch press machine, after which they were heated in a vacuum from 40°C to 360°C over 50 minutes, and as soon as the temperature reached 360°C, a pressure of 12 MPa was applied. After that, the laminates were held at 360°C for 5 minutes, and then cooled to 40°C over 50 minutes, and as soon as the temperature reached 40°C, the pressure was released, yielding a double-sided copper-clad laminate 3 with a dielectric layer thickness of 100 μm.

[0098] Subsequently, the copper foil of the double-sided copper-clad laminate 3 was etched away using an aqueous solution of ferric chloride to prepare a filler-containing resin film 2. The filler-containing resin film 2 had a CTE of 28 ppm / K, a relative dielectric constant of 3.3, a dielectric tangent of 0.0008, and a melting point (Tm) of 324°C.

[0099] (Production Example 4) Dispersion composition 1-4 was applied onto copper foil (1), and then dried using a hot air oven at 80° C. for 1 minute and at 120° C. for 3 minutes. Next, using a hot air oven in a nitrogen atmosphere (oxygen concentration 0.1% by volume or less), the temperature was increased from 40° C. to 240° C. at 10° C. / min, and from 240° C. to 280° C. at 5° C. / min, and the temperature was held at 280° C. for 5 minutes, followed by cooling to 40° C. to obtain a single-sided copper-clad laminate 4.

[0100] Next, two single-sided copper-clad laminates 4 were prepared, and the resin surfaces were placed together in a batch press machine, after which they were heated in a vacuum from 40°C to 280°C over 30 minutes, and as soon as the temperature reached 280°C, a pressure of 12 MPa was applied. After that, the laminate was held at 280°C for 5 minutes, and then cooled to 40°C over 30 minutes, and as soon as the temperature reached 40°C, the pressure was released, thereby obtaining a double-sided copper-clad laminate 4 with a dielectric layer thickness of 100 μm.

[0101] Subsequently, the copper foil of the double-sided copper-clad laminate 4 was etched away using an aqueous solution of ferric chloride to prepare a filler-containing resin film 3. The filler-containing resin film 3 had a CTE of 27 ppm / K, a relative dielectric constant of 3.1, a dielectric loss tangent of 0.0011, and a glass transition point (Tg) of 221°C.

[0102] (Production Example 5) Dispersion composition 1-5 was applied onto copper foil (1), and then dried using a hot air oven at 80° C. for 1 minute and at 120° C. for 3 minutes. Next, using a hot air oven in a nitrogen atmosphere (oxygen concentration 0.1% by volume or less), the temperature was increased from 40° C. to 240° C. at 10° C. / min, and from 240° C. to 280° C. at 5° C. / min, and then the plate was held at 280° C. for 5 minutes, followed by cooling to 40° C. to obtain a single-sided copper-clad laminate 5.

[0103] Next, two single-sided copper-clad laminates 5 were prepared, and the resin surfaces were placed together in a batch press machine, after which they were heated in a vacuum from 40° C. to 280° C. over 30 minutes, and as soon as the temperature reached 280° C., a pressure of 12 MPa was applied. After that, the laminate was held at 280° C. for 5 minutes, and then cooled to 40° C. over 30 minutes. As soon as the temperature reached 40° C., the pressure was released, yielding a double-sided copper-clad laminate 5 with a dielectric layer thickness of 100 μm.

[0104] Subsequently, the copper foil of the double-sided copper-clad laminate 5 was etched away using an aqueous solution of ferric chloride to prepare a filler-containing resin film 4. The filler-containing resin film 4 had a CTE of 52 ppm / K, a relative dielectric constant of 3.1, a dielectric loss tangent of 0.0016, and a glass transition point (Tg) of 220°C.

[0105] (Production Example 6) Polyamic acid varnish (1) was uniformly applied onto copper foil (1) so that the thickness after curing was about 25 μm, and then the coating was dried by heating at 120° C. for 2 minutes to remove the solvent. Further, a stepwise heat treatment was performed from 120° C. to 360° C. for 10 minutes to complete the imidization, and a single-sided copper-clad laminate 6 was obtained.

[0106] Subsequently, the copper foil of the single-sided copper-clad laminate 6 was etched away using an aqueous solution of ferric chloride to prepare a polyimide film (1). The polyimide film (1) had a CTE of 51 ppm / K, a relative dielectric constant of 3.3, a dielectric loss tangent of 0.0027, a glass transition point of 227°C, and a storage modulus at 360°C of 7.5×10 6Pa, and the thermoplastic polyimide had a storage modulus equal to or greater than the above even at temperatures below 360°C.

[0107] <Example 1> After applying polyamic acid varnish (1) as an adhesive layer onto copper foil (1), the coating was dried by heating at 120°C for 1 minute to remove the solvent, and then heat-treated stepwise from 120°C to 360°C for 5 minutes to complete the imidization.

[0108] Next, dispersion composition 1-2 was applied on the adhesive layer as an inorganic filler-containing resin layer, and then dried using a hot air oven at 80° C. for 1 minute and at 120° C. for 3 minutes. Next, using a hot air oven in a nitrogen atmosphere (oxygen concentration 0.1% by volume or less), the temperature was increased from 40° C. to 240° C. at 10° C. / min, and from 240° C. to 360° C. at 5° C. / min, and then the plate was held at 360° C. for 5 minutes, followed by nitrogen heat treatment to cool the plate to 40° C., thereby obtaining a single-sided copper-clad laminate 7.

[0109] Two of the obtained single-sided copper-clad laminates 7 were prepared, and the resin surfaces were placed together in a batch press. The laminates were then heated to 360°C under vacuum. After reaching 360°C, the laminates were pressed at a pressure of 12 MPa for 5 minutes to obtain a double-sided copper-clad laminate 6 having an insulating layer thickness of 100 μm, which is the sum of the adhesive layer and the inorganic filler-containing resin layer. At this time, the thickness of each adhesive layer was 4 μm, the total thickness of the inorganic filler-containing resin layers was 92 μm, and the total thickness of the insulating layers was 100 μm. In addition, no outflow of the resin from the adhesive layers was observed at the ends of the double-sided copper-clad laminate 6. The obtained double-sided copper-clad laminate 6 and the multilayer film 1 from which the copper foil had been removed were evaluated as follows. The evaluation results are shown in Table 1.

[0110] The evaluation results were determined as follows. Peel Strength: 0.7kN / m or more was marked as ○, and less than 0.7kN / m was marked as ×. -Flow of resin from adhesive layer: The maximum amount of resin flowing out of the adhesive layer from the edge of the double-sided copper-clad laminate was less than 1 mm, and the maximum amount of resin flowing out of the adhesive layer from the edge of the double-sided copper-clad laminate was evaluated as ◯, and the maximum amount of resin flowing out of the adhesive layer from the edge of the double-sided copper-clad laminate was evaluated as x. Air gap assessment: When the cross-section was observed by SEM, samples with less than 5 vol.% voids were marked with an ◯, and samples with 5 vol.% or more voids were marked with an ×. ·CTE: Those with a value of 30 ppm / K or less were marked with an ◎, those with a value of more than 30 ppm / K and less than 60 ppm / K were marked with an ○, and those with a value of more than 60 ppm / K were marked with an ×. Dissipation factor: Those less than 0.0020 were rated as ⊚, those less than 0.0025 as ◯, and those 0.0025 or more as ×.

[0111] <Example 2> A single-sided copper-clad laminate 8 and a double-sided copper-clad laminate 7 were produced in the same manner as in Example 1, except that the dispersion composition 1-3 was applied as the inorganic filler-containing resin layer. The copper foil of the double-sided copper-clad laminate 7 was removed to obtain a multilayer film 2. The obtained double-sided copper-clad laminate 7 and multilayer film 2 were evaluated. The evaluation results are shown in Table 1. The evaluation results were determined in the same manner as in Example 1. When the single-sided copper-clad laminate 8 was produced, cracks were observed in part of the surface.

[0112] <Example 3> A single-sided copper-clad laminate 9 and a double-sided copper-clad laminate 8 were produced in the same manner as in Example 1, except that the dispersion composition 1-4 was applied as an inorganic filler-containing resin layer, and the temperature of the nitrogen heat treatment and the press temperature were changed from 360°C to 280°C. The copper foil of the double-sided copper-clad laminate 8 was removed to obtain a multilayer film 3. The obtained double-sided copper-clad laminate 8 and multilayer film 3 were evaluated. The evaluation results are shown in Table 1. The evaluation results were determined in the same manner as in Example 1.

[0113] <Example 4> A single-sided copper-clad laminate 10 and a double-sided copper-clad laminate 9 were produced in the same manner as in Example 3, except that the dispersion composition 1-1 was used as the adhesive layer, the thickness of each adhesive layer was 4 μm, and the total thickness of the inorganic filler-containing resin layer was 92 μm. The copper foil of the double-sided copper-clad laminate 9 was removed to obtain a multilayer film 4. The obtained double-sided copper-clad laminate 9 and multilayer film 4 were evaluated. The evaluation results are shown in Table 1. The evaluation results were determined in the same manner as in Example 1.

[0114] <Example 5> A single-sided copper-clad laminate 11 and a double-sided copper-clad laminate 10 were produced in the same manner as in Example 3, except that the dispersion composition 1-5 was applied as an inorganic filler-containing resin layer. The copper foil of the double-sided copper-clad laminate 10 was removed to obtain a multilayer film 5. The obtained double-sided copper-clad laminate 10 and multilayer film 5 were evaluated. The evaluation results are shown in Table 1. The evaluation results were determined in the same manner as in Example 1.

[0115] <Comparative Example 1> A single-sided copper-clad laminate 12 and a double-sided copper-clad laminate 11 were produced in the same manner as in Example 1, except that the dispersion composition 1-1 was used as the adhesive layer. The copper foil of the double-sided copper-clad laminate 11 was removed to obtain a multilayer film 6. The obtained double-sided copper-clad laminate 11 and multilayer film 6 were evaluated. The evaluation results are shown in Table 1. The evaluation results were determined in the same manner as in Example 1.

[0116] [Table 1]

[0117] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible. [Explanation of symbols]

[0118] Reference Signs List 10A, 10B...metal layers, 20A, 20B...adhesive layers, 30...inorganic filler-containing resin layer, 31...dispersion composition layer, 40...first laminate, 50...second laminate, 100...metal-clad laminate

Claims

1. A metal layer; an adhesive layer directly in contact with the metal layer; an inorganic filler-containing resin layer that contains an inorganic filler in a resin and is laminated directly or indirectly on the adhesive layer; Equipped with The adhesive layer and the inorganic filler-containing resin layer are a) when the main resin constituting the adhesive layer is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer is a crystalline resin, the melting point Tm1 of the main resin constituting the adhesive layer is higher than the melting point Tm2 of the inorganic filler-containing resin layer; b) when the main resin constituting the adhesive layer is a crystalline resin and the main resin constituting the inorganic filler-containing resin layer is an amorphous resin, the melting point Tm1 of the main resin constituting the adhesive layer is higher than the glass transition point Tg2 of the inorganic filler-containing resin layer; c) When the main resin constituting the adhesive layer is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer is a crystalline resin, the storage modulus E' of the adhesive layer at the melting point Tm2 of the inorganic filler-containing resin layer is 1 x 10 6 Pa or more; d) When the main resin constituting the adhesive layer is an amorphous resin and the main resin constituting the inorganic filler-containing resin layer is an amorphous resin, the storage modulus E′ of the adhesive layer at the glass transition temperature Tg2 of the inorganic filler-containing resin layer is 1×10 6 Pa or more; Either of the following conditions is met: The metal-clad laminate has a coefficient of thermal expansion (CTE) of 60 ppm / K or less for the entire insulating layer including the adhesive layer and the inorganic filler-containing resin layer.

2. The metal-clad laminate according to claim 1, wherein the entire insulating layer including the adhesive layer and the inorganic filler-containing resin layer is left for 24 hours under conditions of temperature: 24 to 26°C and humidity: 45 to 55%, and then the dielectric loss tangent at 20 GHz measured with a split post dielectric resonator (SPDR resonator) is less than 0.0025.

3. 2. The metal-clad laminate according to claim 1, having a layer structure in which a metal layer / an adhesive layer / an inorganic filler-containing resin layer / an adhesive layer / a metal layer are laminated in this order.

4. 2. The metal-clad laminate according to claim 1, wherein a ratio of the thickness of the adhesive layer to a total thickness of the adhesive layer and the inorganic filler-containing resin layer is within a range of 1 to 25%.

5. The metal-clad laminate according to claim 1, wherein the inorganic filler-containing resin layer contains a low-elasticity resin that, when formed into a film together with the main resin, has a storage modulus of 2500 MPa or less at 50°C and a maximum storage modulus of 800 MPa or less in the temperature range from 180°C to 260°C.

6. A method for producing the metal-clad laminate according to any one of claims 1 to 5, preparing a first laminate having an adhesive layer laminated on a metal layer; A step of applying a dispersion composition containing an inorganic filler and a powder of the main resin onto the adhesive layer, and heat-treating the dispersion composition to form a second laminate in which the adhesive layer and the dispersion composition layer are laminated on the metal layer; A step of forming a metal-clad laminate having a layer structure in which a metal layer / an adhesive layer / an inorganic filler-containing resin layer / an adhesive layer / a metal layer are laminated in this order by using two of the second laminates and thermocompressing the dispersion composition layers facing each other, or by using the first laminate and the second laminate and thermocompressing the adhesive layer and the dispersion composition layer facing each other; A method for producing a metal-clad laminate comprising the steps of:

Citation Information

Patent Citations

  • High-frequency printed wiring board substrate

    JP6997104B2

Cited By

  • Method for evaluating compatibility of thermosetting resin composition, thermosetting resin composition, prepreg, resin film, laminated plate, multilayer printed wiring board, and semiconductor package

    US20230392002A1